Educating Accountants with a Sustainability-Oriented Professional Identity in Central and Eastern Europe - Cătălin-Nicolae Albu; Çağnur Balsari; Meliha Bašić; Zorica Bozhinovska Lazarevska; Sandra Damijan; Nikolina Dečman; Ivan Dionisijev; Olga Grzybek; Gina Raluca Gușe; Ana Lalević Filipović; Mustafa Oğuz; Ivana Perica; et al. (Amfiteatru Economic, 2025)
This paper has investigated the role that universities may play in shaping a sustainabilityoriented professional identity of accountants, which represents an essential contribution of the paper. A sample of 713 answers collected via an online questionnaire-based survey from prospective accountants in nine countries in Central and Eastern Europe was statistically analysed. This geographical area is largely ignored in the literature. By applying principal component analysis and cluster analysis, the paper documented that universities play a significant role in raising the interest of future accountants in sustainability matters, alongside other stakeholders and the societal and institutional factors. Exposure to sustainability-related activities also helps shape this new identity of future accountants, in conjunction with other education enablers, which should encourage universities to open their curriculum to such matters.